Movie-Making In Singapore - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
When the movie Ah Boys to Men broke the record for the highest-grossing Singapore film in December last year, its producers knew they would, at the very least, avoid making a loss. The S$6.03 million collected at the box office up to that point was twice the S$3 million that was spent to make the movie, so one would think its director, Jack Neo, would be laughing all the way to the bank. One would also be wrong ...